A MACROFORM ANALYSIS TO DESCRIBE THE CITY MORPHOLOGICAL COMPACTNESS FACING THE URBAN SPRAWL PHENOMENON CASE OF BEJAIA CITY - Tebbane Bouktit, K; Alkama, Dj (university of el oued/جامعة الوادي, 2021)
Describing the morphological reality of urban areas is essentia l for any the city ’s sustainability project. Through a comparative analysis based on a series of indices and their confrontation according to the multivariate principal component analysis, we have tried to evaluate from the view point of urban sprawl, the morpho logical compactness of the Algerian coastal Bejaia town. The latter is known to be characterised by physical and natural constraints which influence spatial growth and the process of urban development. The main objective of this article is to establi sh the macroforms classification th at constitute Bejaia city. The configuration analysis ’s results of its urban spots have shown an excessive spread of the agglomeration on the Bejaoui coast, which negatively impacts the city’s sustainability.
Article
Keywords: Keywords: ma crofor m; urban sprawl; form indices; city ’s sustainability; Bejaia.